2013
DOI: 10.1007/s11302-013-9373-4
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan 46 is a site for ethanol and ivermectin action in P2X4 receptors

Abstract: ATP-gated purinergic P2X4 receptors (P2X4Rs) are the most alcohol-sensitive P2XR subtype. We recently reported that ivermectin (IVM), an antiparasitic used in animals and humans, antagonized ethanol inhibition of P2X4Rs. Furthermore, IVM reduced ethanol intake in mice. The first molecular model of the rat P2X4R, built onto the Xray crystal structure of zebrafish P2X4R, revealed an action pocket for both ethanol and IVM formed by Asp331, Met336 in TM2 and Trp46, and Trp50 in TM1 segments. The role of Asp331 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
59
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(67 citation statements)
references
References 45 publications
(103 reference statements)
8
59
0
Order By: Relevance
“…In contrast, chimeras of the two transmembrane segments of rP2X4 receptor into rP2X2 receptor are sufficient to confer IVM sensitivity (Silberberg et al, 2007), indicating a major role of both transmembrane segments of P2X4 receptor in the positive allosteric effect of the modulator. Consistent with a transmembrane location, site-directed mutagenesis analysis of residues located in the putative TM domains (Jelinkova et al, 2008;Popova et al, 2013;Silberberg et al, 2007) indicated that V28, Q36, I39, L40, Y42, V43, V47, W50 (TM1) and N338, G340, G342, L345, L346, V348, A349, I356 (TM2) in rP2X4 are involved in IVM sensitivity of the channel (Jelinkova et al, 2008;Silberberg et al, 2007). A recent study confirmed the importance of some of these residues (L40, V43, V47 and W50) in the effect of IVM on deactivation in rP2X4, and further identified new ones (W46, G53, F330, D331, I332 and I337) (Zemkova et al, 2015).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 87%
See 3 more Smart Citations
“…In contrast, chimeras of the two transmembrane segments of rP2X4 receptor into rP2X2 receptor are sufficient to confer IVM sensitivity (Silberberg et al, 2007), indicating a major role of both transmembrane segments of P2X4 receptor in the positive allosteric effect of the modulator. Consistent with a transmembrane location, site-directed mutagenesis analysis of residues located in the putative TM domains (Jelinkova et al, 2008;Popova et al, 2013;Silberberg et al, 2007) indicated that V28, Q36, I39, L40, Y42, V43, V47, W50 (TM1) and N338, G340, G342, L345, L346, V348, A349, I356 (TM2) in rP2X4 are involved in IVM sensitivity of the channel (Jelinkova et al, 2008;Silberberg et al, 2007). A recent study confirmed the importance of some of these residues (L40, V43, V47 and W50) in the effect of IVM on deactivation in rP2X4, and further identified new ones (W46, G53, F330, D331, I332 and I337) (Zemkova et al, 2015).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 87%
“…In support of this hypothesis, mutations of the amino acid W46 to other aromatic residues (tyrosine or phenylalanine) in heterologously expressed rP2X4 receptor did not modify IVM-induced potentiation of ATP-dependent currents, whereas substitution with nonaromatic residues (leucine, valine, alanine, asparagine, lysine or aspartate) switched the potentiation to inhibition (Popova et al, 2013). Therefore, it has been suggested that the presence of an aromatic group at position 46 is a critical determinant of IVM-induced allosteric effects, most probably by means of a cation-π interaction (Popova et al, 2013).…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…NF770, a suramin derivative that competitively inhibits the P2X2 receptor at nanomolar concentrations, acts on G72, E167 and R290 (rP2X2 numbering), which are also important for ATP binding [112,113] . Interestingly, nearly all of those identified sites are located in or around the ATP binding pocket except for IVM, a P2X4 positive modulator, which has been identified to act on the TM domains [114][115][116][117] .…”
Section: Small Molecules To Change the Channel Gating Of P2x Receptorsmentioning
confidence: 99%